Evaluation of the psychometric properties of the family adaptability and cohesion scale (FACES III) through item response theory models in students from Chile and Colombia - Lindsey W. Vilca; Víctor Díaz-Narváez; Wilson Pastén Hidalgo; Nicolás Van Niekerk Bakit; Paula Moreno Reyes; Yaneth Herazo-Beltrán; Aura Gauna-Quiñonez; Alejandro Reyes-Reyes; Luz Marina Alonso Palacio; Marco Cervantes Mendoza (BMC Psychology, 2024)
Abstract Background A psychometric study of the Family Adaptability and Cohesion Scale (FACES III) has been conducted in Spanish-speaking countries from the perspective of the classical test theory. However, this approach has limitations that affect the psychometric understanding of this scale. Objective Accordingly, this study used the item response theory to investigate the psychometric performance of the items. Furthermore, it evaluated the differential performance of the items for Colombia and Chile. Method For this purpose, 518 health science students from both countries participated. Confirmatory Factor Analysis was used. Results The study results revealed that the cohesion and adaptability items presented adequate discrimination and difficulty indices. In addition, items 5, 8, 13, 17, and 19 of cohesion indicated differential functioning between students from both countries, with Chilean students exhibiting a greater discriminatory power. Further, the Colombian group exhibited a greater discriminatory power for item 18 of adaptability. Conclusions The study concluded that the items of FACES III indicated adequate psychometric performance in terms of their discriminative capacity and difficulty in Chile and Colombia.